The Job of Citizenship - Earle, Genevieve B. (Tufts Archival Research Center, 2006)
Genevieve B. Earle remembers the surprise of seeing poverty as a child and how she developed a belief in the benefits of a strong government to promote laws and provide for its citizens although she says that can only happen when the people are engaged as active, equal partners in the work of a city.